Мы и наша семья: Кн. для молодых супругов: (Сборник) (Мол. гвардия, 1988)
Экземпляры: ф-5 (ретроконверсия) / Инвентарный номер: 23489 / Цена: 1.20 / Сис.шифр: 87.71 / Авт.знак: М94 / ГРНТИ: 02 / ББК: 87.715